1991
DOI: 10.1095/biolreprod45.1.178
|View full text |Cite
|
Sign up to set email alerts
|

Fertility of Transgenic Female Mice Expressing Bovine Growth Hormone or Human Growth Hormone Variant Genes1

Abstract: Although growth hormone (GH) exerts various direct and indirect stimulatory effects on gonadal development and function, excessive levels of GH in acromegalic patients and in transgenic animals are often associated with reproductive disorders. We have examined reproductive performance of transgenic female mice expressing the following hybrid genes: mouse metallothionein-1 (MT)/human placental GH variant (hGH.V), MT/bovine GH(bGH), and phosphoenolpyruvate carboxykinase (PEPCK)/bGH. This allowed us to evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 0 publications
5
55
1
Order By: Relevance
“…In sharp contrast, mice overexpressing G H live significantly shortened lives, exhibit increased indices of free radical processes (66), decreased antioxidative defenses (14,67), signs of accelerated aging including reduced replicative potential of cells in vitro (75), and signs of premature central nervous system aging including reduced catecholamine turnover, increased astrogliosis, and impaired learning and memory (19,76,77). In addition, these animals typically reach sexual maturation earlier and cessation of reproduction sooner than wild type siblings (21,78). According to Kajiura and Rollo (79), the increased rate of physiological decline in mice overexpressing GH maybe due to a disproportional allocation of energy towards growth versus repair mechanisms, reproduction and behavioral activities.…”
Section: Discussionmentioning
confidence: 99%
“…In sharp contrast, mice overexpressing G H live significantly shortened lives, exhibit increased indices of free radical processes (66), decreased antioxidative defenses (14,67), signs of accelerated aging including reduced replicative potential of cells in vitro (75), and signs of premature central nervous system aging including reduced catecholamine turnover, increased astrogliosis, and impaired learning and memory (19,76,77). In addition, these animals typically reach sexual maturation earlier and cessation of reproduction sooner than wild type siblings (21,78). According to Kajiura and Rollo (79), the increased rate of physiological decline in mice overexpressing GH maybe due to a disproportional allocation of energy towards growth versus repair mechanisms, reproduction and behavioral activities.…”
Section: Discussionmentioning
confidence: 99%
“…These mice have high circulating GH levels and live half as long (12 months) as wild type siblings (Steger et al, 1993). Female GH transgenic mice exhibit early puberty and increased ovulation rates; however, fertility is reduced and the reproductive life span is severely shortened when compared to wild-type mice (degree of suppression appears to depend on level of circulating GH; Naar et al, 1991;Bartke et al, 1994;Cecim et al, 1995). Male mice with elevated GH levels are fertile, but exhibit alterations in sexual behavior, reproductive pituitary hormone secretion, and a reduced reproductive life span (Chandrashekar et al, 1988;Meliska et al, 1997).…”
Section: Growth Hormone/insulin-like Growth Factor 1/insulinmentioning
confidence: 99%
“…Coincident with the increased growth, infertility or subfertility (i.e., less successful matings, gestational failure, etc.) have frequently been observed (Hammer et al, 1984;Morello et al, 1986;Bartke et al, 1988;Purse1 et al, 1989;Bchini et al, 1991;Naar et al, 1991). The nature of the cause(s) of the subiinfertility is not well understood.…”
Section: Growth Hormone and Reproductionmentioning
confidence: 99%
“…The nature of the cause(s) of the subiinfertility is not well understood. Naar et al (1991) reported varying degrees of impairment of female reproductive functions in mice transgenic for three different GH fusion genes. The highest degree of infertility (65%) was observed in mice expressing a phosphoenolpyruvate carboxykinase-bovine GH (PEPCK-bGH) gene in which plasma levels of bGH were >ZOO ng/ml.…”
Section: Growth Hormone and Reproductionmentioning
confidence: 99%